Thematic unit "Tissues" in grammar school biology - Bystrá, Veronika; Čečmanová, Adéla; Dvořáková, Radka Marta; Váňová, Barbora; Novotný, Petr (Scientia in educatione, 2023)
For the chosen thematic unit of grammar school biology “Tissues” we designed a conceptual framework, identified the core curriculum used in textbooks, and designed test items to verify the understanding of the defined concepts. The conceptual framework was designed based on the of Czech grammar school biology textbooks and supplementary materials. It contains ten core concepts, the understanding of which is considered to be the aim and reason for teaching a given thematic unit. From the textbooks, we have excerpted the content used to build an understanding of these concepts. Thanks to the insight gained, we were able to describe didactically interesting aspects of this topic in Czech textbooks. In most of them, the unit “Tissues” form the gateway to the organology of the human body. Based on the conceptual framework and the intended curriculum, we designed test items. The items were validated in three grammar schools, and their analysis was based on Classical Test Theory and Item Response Theory. The resulting set contains 33 psychometrically validated test items published under a CC BY-SA 3.0 license, which are included as an appendix to this article.